EFFECT OF LATEX FROM MUSA PARADISIACA VAR. SAPIENTUM AND CARICA PAPAYA L. ON PROLIFERATION AND MIGRATION FIBROBLAST CELL NIH3T3 - SUNDHANI, ELZA; IROHIM, ENDAH NUR; HARTININGSIH, RUMIYANA; GENATRIKA, ERZA; NURULITA, NUNUK ARIES (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research was to screen phytochemical constituents and determine the activity of latex from Musa paradisiaca var. sapientum and Carica papaya L. to the process of wound healing in NIH3T3 fibroblasts cells through observations of the proliferation and migration of cells. Materials and Methods: Screening phytochemical compounds of latex from M. paradisiaca var. sapientum and C. papaya L. used chemical reagent. Cytotoxic activity using 3-(4,5-dimethylthiazol-2-yl)-2.5-diphenyl tetrazolium bromide (MTT) method. The proliferation test used the doubling time method at a susceptible incubation time of 0, 24, 48, and 72 h with a concentration of 25 μg/mL–250 μg/mL. The migration test was carried out using the scratch wound healing method with a concentration of 25 μg/mL–250 μg/mL in the time range of 0, 12, 24, and 48 h. Results: Phytochemical compounds contained in the latex from M. paradisiaca var. sapientum (saponin and tannin) and C. papaya L. (saponin and alkaloid). The cytotoxic assay results showed that no toxic effect for NIH3T3 fibroblasts cells (IC50 >1000 μg/mL). Cell proliferation and migration test results showed an increase in NIH3T3 fibroblast cell proliferation and migration process compared to controls. The concentration of 250 μg/mL of latex from M. paradisiaca var. sapientum and C. papaya L. is the best to increase of proliferation and migration process of NIH3T3 fibroblast cells. Conclusion: This study concludes that the latex of M. paradisiaca var. sapientum and C. papaya L. has the potential to increase proliferation and migration activity of NIH3T3 cells.